Long head of biceps in proximal fractures of the humerus: an underestimated problem? Critical analysis and review of the literature - Branca Vergano, Luigi; Corsini , Giovanni; Monesi , Mauro (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The long head of biceps (LHB) is one of the tendons of the rotator cuff that runs strictly close to the humeral head. In case of pathology, it can be responsible for pain and shoulder impairment: in such cases, surgical options include tenotomy or tenodesis. The management of LHB along with surgery of the rotator cuff or during shoulder prosthetic replacement has been widely discussed in the literature. Conversely, the possibility of acute impingement and incarceration of LHB in proximal humerus fractures, as well as its role in shoulder pain in outcomes of these fractures, has been poorly considered. Methods: The following aspects in the literature on LHB and proximal humerus fractures have been analysed: its management during fixation of fractures, the possibility of interference of the tendon with reduction of fractures or dislocations of the shoulder and its possible role in chronic pain after fixation of proximal humerus fractures. Results: LHB can be an obstacle in the reduction of fractures, dislocations and fracture-dislocations. Only a few papers take into account acute surgery to LHB (tenotomy or tenodesis); most of the studies on fixation of proximal humerus fractures simply ignore the problem of LHB. The tendon can be a source of pain and a cause of disability in sequelae of these fractures. Conclusions: LHB should be taken into consideration both in the acute phase of fractures of the proximal humerus and in the outcomes. Other studies are needed to better understand its optimal management during fracture surgery.